Distribution of Hatschekia pagellibogneravei (Copepoda: Hatschekiidae) on the gills of Pagellus bogaraveo (Teleostei: Sparidae) from Madeira, Portugal - Hermida, Margarida; Cruz, Cristina; Saraiva, Aurélia (Folia parasitologica, 2012)
A population of the gill parasite Hatschekia pagellibogneravei (Hesse, 1878) was studied on one of its sparid fish hosts, the blackspot seabream, Pagellus bogaraveo (Brünnich), off the coast of Madeira Island, Portugal, northeast Atlantic. Very high infection levels of this copepod were detected, with no significant seasonal differences. Abundance was negatively correlated with fish size. There were significant differences in the distribution of this copepod among the gill arches of the host, which seem to be best explained by differences in water flow within the gill habitat.
Keywords: Perciformes; Animals; nemoci ryb; Gills; zvířata; Host-Parasite Interactions; Fish Diseases; Portugalsko; interakce hostitele a parazita; žábry; Portugal; Copepoda